2020
DOI: 10.1111/medu.14423
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous motivation explains interprofessional education outcomes

Abstract: Objectives In response to the observations that interprofessional education (IPE) is seemingly atheoretical or under‐theorised, this quantitative research seeks to uncover students’ motivational mechanisms which could explain their behavioural and collaborative outcomes using self‐determination theory (SDT). While SDT has been studied in various contexts, its applicability to IPE remains underexplored. This study aims to integrate a new perspective in understanding students’ motivation in IPE by exploring how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…This refers to students’ perception of how IPE allowed them to achieve collaboration competencies [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This refers to students’ perception of how IPE allowed them to achieve collaboration competencies [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we used the instrument adapted and validated in Study 1, the BPNS-IPE, to examine the theoretical link between psychological needs satisfaction (autonomy, competence, and relatedness) in predicting team cohesiveness in IPE. Further, this aims to provide generalizability to the earlier study of Ganotice et al [ 17 ] on how psychological need satisfaction can predict IPE outcomes using a different set of samples.…”
Section: Study 2: Application Of Sdt In Ipe Contextmentioning
confidence: 97%
See 1 more Smart Citation
“…Although widely applied, neither SDT specifically nor consideration of motivation more generally has received a lot of attention in the context of interprofessional education (IPE) 3 . This issue of Medical Education provides a counter example as Ganotice et al attempt to change the narrative by delving into the relationship between motivation and interprofessional education for 3rd year medicine, nursing and pharmacy students 4 . Interprofessional education is defined as the process whereby two or more professions learn with, from and about each other 5 .…”
mentioning
confidence: 99%
“…Such activity is often used in universities and health care facilities to address the complex training needs of the health professions 5 . Ganotice et al hypothesised that the fulfilment of the three needs identified in SDT in the context of interprofessional education would lead to greater satisfaction with interprofessional goals 4 . They found that autonomy in particular was related to team effectiveness, collective dedication, behavioural engagement and goal achievement in the interprofessional education context 4 …”
mentioning
confidence: 99%